Termogênese e distribuição de calor pela cria de abelhas sem ferrão e sua relação com o estágio de desenvolvimento em ambiente semiárido - Dantas, Maiko Roberto Tavares (2014)
The study of thermoregulation in stingless bees (Hymenoptera, Apidae, Meliponini) is essential to better understand the adaptation of these insects to the environment to which they are inserted. Its physiological behavior regarding different temperatures helps to understand the evolution of their society. The mechanisms of thermal exchanges are important strategies to ensure the survival of a species, especially for the more immature individuals, ie the brood. This work was conducted at the Experimental Field Station "Rafael Fernandes", belonging to UFERSA in Mossoró-RN, Caatinga biome. 10 brood combs of Melipona subnitida were analyzed by thermography and measured the temperatures of the surfaces of cells separated into 10 categories, divided into seven different brood's stages of development, cells with dead individuals, empty cells and cells containing larvae and pupae of the parasite Plega hagenella. The combs were analyzed in a BOD incubator with a digital thermographic camera FLIR (Series SC620). It was found that the contribution of metabolic heat by category and what differences occurred in thermogenesis within categories in different ranges of temperature (20 ºC, 25 ºC, 30 ºC and 35 ºC). Was Used as ambient temperature, the mean temperatures of the surrounding area to comb situated at 4cm from this and compared with the mean surface temperature (Tsc) of each category. The older stages of development showed greater thermogenesis than the younger, and the temperature range that had the highest mean gains of heat was at 35 °C with 0,38 °C (TOv) and 0,61 °C (TP3) as minimum and maximum, respectively. From range of 25 ºC, all categories showed means Tsc higher than their respective mean ambient temperatures. The mean temperature of the brood comb tends to increase the higher the number of cells containing older stages and decrease when there is the presence of younger individuals. Larvae and pupae contribute to their own thermoregulation through its thermogenesis, which is the only mechanism for heat production by the brood